From Stall to Screen: Increasing MSMEs Exposure and Sales in Pering Village Through Online Marketing - Dewi, Sayu Ketut Sutrisna; Sukawati, Tjokorda Gde Raka; Seminar, Ni Ketut; Martins, Rosena Fatima De Oliveira; Adyatma, Prastha; Sumariani, Ni Putu Ayu; Geriadi, Made Ayu Desy; Artha, I Kadek Arifandi Werdhi; Putri, Putu Amanda Angelina (Transpublika Publisher, 2025)
Limited marketing access remains a major obstacle for Micro, Small, and Medium Enterprises (MSMEs) in Pering Village, Blahbatuh District, Gianyar Regency, Bali Province, leading to low sales volumes and profits. Although these enterprises have the potential to produce various superior products, their market reach is constrained, partly because digital technology is still used primarily for personal rather than business communication. To address this issue, a community service program was implemented that included digital marketing training, product photography assistance, the development of compelling promotional narratives, and support in creating business accounts on appropriate digital platforms. The program has enabled MSME actors to expand their marketing access and become more prepared to compete in the digital marketplace, thereby supporting increased sales performance and business growth. Participants improved their digital marketing skills, creating better product photos and promotions. They applied this knowledge by setting up Google Business profiles and social media accounts, expanding their online presence.